2019
DOI: 10.1111/cas.14235
|View full text |Cite
|
Sign up to set email alerts
|

Kinase activity of ERBB3 contributes to intestinal organoids growth and intestinal tumorigenesis

Abstract: As a member of the epidermal growth factor receptor (EGFR) family, ERBB3 plays an essential role in development and disease independent of inherently inactive kinase domain. Recently, ERBB3 has been found to bind to ATP and has catalytic activity in vitro. However, the biological function of ERBB3 kinase activity remains elusive in vivo. Here we have identified the physiological function of inactivated ERBB3 kinase activity by creating Erbb3‐K740M knockin mice in which ATP cannot bind to ERBB3. Unlike Erbb3 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Unlike Erbb3 V943R/V943R mice, we found that mice bearing D850N mutation ( Erbb3 D850N/D850N ) in the canonical “DFG” motif of the ERBB3 kinase domain, that is expected to abolish any residual kinase activity developed normally. Consistent with our findings, a recent study reported normal development of a kinase‐dead ERBB3 K740M variant knock‐in mouse 61 . These findings, together with the functional defects observed for the ERBB3 V943R mutant, indicate that ERBB3 primarily functions as an allosteric activator during tissue morphogenesis, and that its reported weak kinase activity are dispensable for its key physiological function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike Erbb3 V943R/V943R mice, we found that mice bearing D850N mutation ( Erbb3 D850N/D850N ) in the canonical “DFG” motif of the ERBB3 kinase domain, that is expected to abolish any residual kinase activity developed normally. Consistent with our findings, a recent study reported normal development of a kinase‐dead ERBB3 K740M variant knock‐in mouse 61 . These findings, together with the functional defects observed for the ERBB3 V943R mutant, indicate that ERBB3 primarily functions as an allosteric activator during tissue morphogenesis, and that its reported weak kinase activity are dispensable for its key physiological function.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, a recent study reported normal development of a kinase-dead ERBB3 K740M variant knock-in mouse. 61 These findings, together with the functional defects observed for the ERBB3 V943R mutant, indicate that ERBB3 primarily functions as an allosteric activator during tissue morphogenesis, and that its reported weak kinase activity are dispensable for its key physiological function. Our Erbb3 CKI-V943R mice will be an important tool to test and clarify the relevance of ERBB3 in ERBB2 driven tumorigenesis and drug targeting.…”
Section: Discussionmentioning
confidence: 87%
“…P53 loss alone ( Takeda et al, 2019 ) or QKI-5 (a transcriptional target of P53) decline in expression ( Mukohyama et al, 2019 ) confers the metastatic ability to intestinal tumors. Nguyen et al ( Nguyen et al, 2020 ) found that ERBB3 (a member of the EGFR) kinase activities contribute to the outgrowth of epithelial cells under NRG1-β1 exposure, which is usually overexpressed in colon cancers. Hu et al ( Hu et al, 2020 ) found that Dachshund homologue 1 reduces the phosphorylation of Smad4 and inhibits the BMP pathway through its interaction with Smad, thereby promoting the formation and stemness of CRC organoids.…”
Section: Application Of Organoids In Crc Researchmentioning
confidence: 99%
“…Several research groups have successfully established colorectal cancer (CRC) organoids [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Patient‐derived CRC organoids have been used to find associations between stem cell markers, patient survival, and resistance to therapy [ 49 , 60 ].…”
Section: Applications Of Organoids In Various Types Of Cancermentioning
confidence: 99%